THE ROLE OF INNOVATIVE MARKETING IN PROMOTING GREEN CONSUMER BEHAVIOR: ANALYTICAL STUDY OF A SAMPLE OF CUSTOMERS OF AL-QADISIYAH DAIRY FACTORY (World Bulletin of Management and Law, 2022)
The aim of the research is to find out whether there is a strong relationship between Innovative Marketing And Green Consumer Behavior For a Sample of Consumers of Qadisiyah Dairy Factory Products. Design / Methodology: The Data Was Collected Through A Questionnaire Distributed Electronically Through Social Networking Sites to A Random Sample of (200) Single Customers of Al-Qadisiyah Dairy Factory. After Examining The Forms, The (20) Incomplete And Invalid Forms For Analysis Were Excluded, Thus, The forms to be analyzed Is (180) Questionnaires, A Set of Statistical Methods Were Used to Analyze Data And Test Hypotheses Using The Statistical Program (SPSS.V.25)..
Keywords: Innovative Marketing; Green Consumer Behavior; Promotion Innovation